Pengaruh market orientation dan networking terhadap kinerja usaha industri makanan oleh-oleh - Muhammad Aidil; Thamrin Thamrin (Jurnal Kajian Manajemen dan Wirausaha, 2020)
The purpose of this study was to analyze: (1) The effect of market orientation on the performance of the food industry souvenir business in Padang City (2) The effect of Networking on the performance of the food industry souvenir business in Padang City.  This type of research is causative. The population in this study is the food industry souvenirs in the city of Padang, which is registered in the Department of Labor and Industry of the City of Padang. The total sample in this research is 30 MSMEs. This study shows that (1) Market Orientation has a significant effect on the performance of the souvenir industry business in Padang (2) Networking has a significant effect on the performance of the souvenir industry business in Padang.So, market orientation and networking have a significant effect on business performance. Market orientation and Networking both have the most influence on business performance in this study. For further research, it is expected to find more variables about business performance.  Keywords: Market orientation, networking